Steganalysis algorithm for images that have been lossy compressed - Рудницький, Володимир Миколайович; Узун, Ілля Афанасійович (Ukrainian Information Security Research Journal, 2013)
Easy to use, and also a lot of software tools both paid and free, freely distributed on network, made steganography very popular tool by which you can provide a simple way of diversion of valuable information and uncontrolled exchange of information for illegal purposes. These circumstances make greater efforts to develop algorithms for steganalysis. One type of such algorithms are algorithms that are based on the analysis of color pairs of digital images. Most of the existing similar means focused on working with images that are stored in a lossless format, which significantly narrows the scope of their application. Taking this into account in the steganalysis algorithm has been proposed for determining presence a secret message embedded into digital image which has been lossy compressed, using method of least significant bit. The results showed that the principle of the analysis color pairs can be successfully applied for steganalysis digital image is subjected to a lossy compression.